Isometric handgrip exercise during cardiovascular magnetic resonance imaging: Set‐up and cardiovascular effects. Issue 6 (24th January 2013) - von Knobelsdorff‐Brenkenhoff, Florian; Dieringer, Matthias A.; Fuchs, Katharina; Hezel, Fabian; Niendorf, Thoralf; Schulz‐Menger, Jeanette
Abstract Purpose: To establish a suitable setup for combining isometric handgrip exercise with cardiovascular magnetic resonance (CMR) imaging and to assess cardiovascular effects. Materials and Methods: Fifty‐three healthy volunteers (31 males, mean age 45 ± 17 years) underwent handgrip exercise in a 3T scanner using a prototype handgrip system and a custom‐made feedback system that displayed the force. Handgrip was sustained at 30% of the maximal contraction for 6–8 minutes. Heart rate, blood pressure (BP), and double product were determined sequentially. Stroke volume was quantified in a subgroup (n = 21) at rest and stress using phase contrast acquisitions. Results: Heart rate increased significantly between rest and stress by 20 ± 13%, systolic / diastolic / mean BP by 15 ± 11% / 20 ± 18% / 17 ± 13%, double product by 37 ± 21%, and cardiac output by 27 ± 16% (each P < 0.001). Stroke volume did not significantly increase (3 ± 9%; P = 0.215). Higher age was associated with reduced increase of stroke volume (P = 0.022) and cardiac output (P < 0.001). Overweight subjects showed less increases in heart rate (P = 0.021) and cardiac output (P = 0.002). Conclusion: The handgrip exercise during CMR with the presented set‐up leads to considerable hemodynamic changes in healthy volunteers. J. Magn. Reson. Imaging 2013;37:1342–1350. © 2013 Wiley Periodicals, Inc.